The Relationship Between Stigma and Family Support on the Psychosocial Adaptation of HIV/AIDS Patients - Aurora Almira Darwanto; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (International Journal Of Health Science, 2026)
HIV/AIDS (Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome) is a serious illness caused by the HIV virus, which attacks the immune system, leading to high morbidity and mortality. HIV cases in Indonesia reached an estimated 503,201 people in 2024. In addition to biological challenges, people living with HIV/AIDS (PLWHA) face severe psychosocial stress, primarily due to stigma and discrimination within both the family and the wider community. Therefore, the critical aspect of psychosocial adaptation requires a holistic approach, particularly through family support, to reduce stigma and ensure PLWHA receive optimal support. To determine the relationship between stigma and family support on the psychosocial adaptation of HIV/AIDS patients. This study used a quantitative research approach with a cross-sectional design. The sample consisted of 79 respondents. Sampling was determined using the accidental sampling technique. The data obtained were analyzed using the Spearman's rho correlation test. The results of the Spearman's rho correlation test indicate a relationship between stigma and family support on the psychosocial adaptation of HIV/AIDS patients. A relationship exists between stigma and family support on the psychosocial adaptation of HIV/AIDS patients.